Adipose tissue derived mesenchymal stem cell transplantation in the treatment of ischemia/reperfusion induced acute kidney injury in rats. Application route and therapeutic window - Monteiro,Betânia Souza (2018)
Abstract Purpose: To evaluate renal repair in rats who had renal infarction induced by the obstruction of blood flow in the renal artery and were treated with transplantation of adipose tissue derived mesenchymal stem cell Methods: 16-week-old Wistar rats (n=72) were used, submitted to celiotomy and had of the renal artery and vein clipped for 24 hours. The animals were randomly assigned to 10 experimental homogeneous groups, corresponding to the treatments with phosphate-buffered saline (PBS) or adipose tissue derived mesenchymal stem cell (ADSC), duration of application (24 or 48 hours), and site of transplantation (lateral vein of the tail or intrarenal). After the treatments were performed, at 8 and 31 days, four animals in each group were subjected to left nephrectomy for histological studies. Results: Histologically, a higher amount of cell debris and tubules devoid of the epithelium and a higher degree of necrosis were observed in the groups treated with PBS, as opposed to a low degree of necrosis and higher tubular vascularization in the groups treated with ADSC, particularly in the group treated with intrarenal ADSC 48 hours after injury. Conclusion: The transplantation of ADSC positively contributed to the replacement of necrotic tissue by renal tubular cells, vascularization of the renal parenchyma, and restoration of the organ function.